Development of E-Student Worksheets in the form of Picture Stories Using Live Worksheets in Primary Schools - Marwan Pulungan; Siti Dewi Maharani; Evy Ratna Kartika Waty; Mazda Leva Okta Safitri; Vina Amalia Suganda; Fadhilah Tu Husni (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The article aimed to determine the feasibility and effectiveness of the products developed, that was E-Student Worksheets in the form of Picture Stories Using Live Worksheets at Elementary Schools. The type of research used Research and Development (R&D). The research procedure used Rowntree development with three stages, namely planning, development and assessment. The product developed has been declared feasible to use according to the validation results from material experts, media experts, and design experts. In field trials, it was found that the use of e-student worksheets in the form of illustrated stories using live worksheets, made students happier to learn, interested in learning, and made it easier for students to understand the learning material. The E-Student Worksheets in the Form of Picture Stories using the developed live worksheet could be said to be feasible and effective to use. This research was useful as a reference for the use of technology for educators in providing variations of worksheets to students. This live worksheet was also useful in making it easier for educators to check the work of students and students are also given the convenience of collecting their worksheets without being limited by distance. This research was useful as a reference for the use of technology for educators in providing variations of worksheets to students. Keywords: E-Student Worksheets, Picture Stories, Development Worksheets